Electric field study with HIBP in OH and ECRH plasmas on the T-10 tokamak - Melnikov, A.V.; Dyabilin, K.S.; Eliseev, L.G.; Grashin, S.A.; Isaev, M.Yu.; Krupnik, L.I.; Lysenko, S.E.; Mavrin, V.A.; Perfilov, S.V.; Ryzhakov, D.V.; Zenin, V.N. (Вопросы атомной науки и техники, 2013)
The plasma potential φ and radial electric field Er were studied on T-10 in a wide range of ohmic and ECRH regimes. At densities ne> 10¹⁹ m⁻³, the potential has negative sign over the whole plasma cross section. At lower densities, the outer zone with positive φ and Er is formed. The absolute value of potential at mid-radius grows with density up to ne ≈ 3×10¹⁹ m⁻³ and then saturates. In regimes with ECR heating, |φ| decreases owing to the density pump-out and the electron temperature increase. Measurements of Er are compared with numerical simulations with several codes including nonambipolar fluxes due to the toroidal field ripple. The change of radially averaged ¬Er with density and temperature qualitatively agrees with neoclassical expectations. Потенциал плазмы φ и радиальное электрическое поле Er исследовались на токамаке T-10 в широком диапазоне омических и ЭЦР-режимов. При плотностях ne> 10¹⁹ м⁻³ потенциал имеет положительный знак во всем сечении плазмы. При меньших плотностях во внешней зоне потенциал и Er меняют знак. Абсолютное значение потенциала на середине радиуса растет с плотностью вплоть до ne ≈ 3×10¹⁹ м⁻³, а затем насыщается. В режимах с ЭЦР-нагревом абсолютная величина |φ| уменьшается за счет откачки плотности и роста электронной температуры. Измерения Er сравнивались с численными расчетами по нескольким кодам, учитывающим неамбиполярные потоки за счет гофрировки тороидального поля. Изменение среднего поля ¬Er с плотностью и температурой не противоречит неоклассическим ожиданиям. Потенціал плазми φ та радіальне електричне поле Er було досліджено на токамаці Т-10 у широкому діапазоні омічних та ЕЦР-режимів. При щiльностях ne> 10¹⁹ м⁻³ потенцiал має позитивний знак в усьому перетинi плазми. При менших щiльностях у зовнiшнiй зонi потенціал та Er змiнюють знак. Абсолютне значення потенцiалу на серединi радіуса росте зi щiльністью майже до ne ≈ 3×10¹⁹ м⁻³, а потiм насичується. У режимах з ЕЦР-нагрiвом абсолютна величина |φ|зменшується за рахунок відкачки щiльностi та росту електронноï температури. Вимiрювання Er порiвнювалися з числовими розрахунками за декiлькома кодами, які враховують неамбіполярнi потоки за рахунок гофрировки тороïдального поля. Зміна середнього поля ¬Er з щiльнiстю та температурою не протирiчить неокласичним сподiванням.